Efficient Stubborn Sets: Generalized Algorithms and Selection Strategies - Wehrle, Martin; Helmert, Malte (Proceedings of the International Conference on Automated Planning and Scheduling, 2014)
Strong stubborn sets have recently been analyzed and successfully applied as a pruning technique for planning as heuristic search. Strong stubborn sets are defined declaratively as constraints over operator sets. We show how these constraints can be relaxed to offer more freedom in choosing stubborn sets while maintaining the correctness and optimality of the approach. In general, many operator sets satisfy the definition of stubborn sets. We study different strategies for selecting among these possibilities and show that existing approaches can be considerably improved by rather simple strategies, eliminating most of the overhead of the previous state of the art.